25–53 GHz ultra‐wideband high‐isolation passive balanced duplexer on 0.18‐μm BiCMOS for 5G applications. Issue 15 (22nd October 2020) - Hsiao, Meng‐Jie; Nguyen, Cam
Abstract : A new ultra‐wideband millimetre‐wave passive balanced duplexer (DUX), employing a lumped‐element Wilkinson power divider and grounded‐centre‐tap transformer, has been developed using 0.18‐ μ m BiCMOS process for fifth generation operations at 28, 37, 39 GHz, and beyond. The developed DUX is configured single‐ended transmitter (TX) and antenna (ANT) ports and differential receiver (RX) port. It has an inherent matching at TX, RX and ANT ports, high TX–RX isolation, and highly balanced differential RX waveforms, and is ready for direct integration with a differential low‐noise amplifier. Analysis has been performed to confirm the DUX's characteristics and assess its performance. Measured isolation from TX to each single‐ended RX port is higher than 50 and 40 dB from dc‐20 GHz and dc‐60 GHz, respectively. Measured insertion loss from TX to antenna is better than 6.3 dB across 13–53 GHz. Measured insertion loss from ANT to differential RX port is lower than 13.8 dB from 25 to 57 GHz with 10.8 dB at 40 GHz. The core chip only occupies 0.3 mm 2 .